Sistem Informasi Pengumpulan Data Siswa Baru SD Negeri 15 Batu Nanggai - Muhammad Ridho; Rohaniatul Husna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Admission of new students is an important process in the world of education that requires efficiency, accuracy and good data management. However, in many institutions, this process is still carried out manually so it is susceptible to recording errors, data duplication, and takes quite a long time. One of them is at SDN 15 Batu Nanggai. This research aims to design and build a new computerized student data collection information system to support the registration process more effectively and efficiently which will later be useful for dapodik operators in meeting data needs for student administration. This system was built using web-based technology with main features such as online form filling, automatic data verification, and data storage in a structured database. By implementing this system, it is hoped that it can increase the speed of the data collection process at SDN 15 Batu Nanggai, minimize data input errors, and make it easier for the school to manage new student information in real-time. The test results show that the system is able to work well and is well received by users as a digital solution that facilitates the administrative process of collecting new student data at SDN 15 Batu Nanggai.